Entre vanguardas: outro lado de uma mesma geração modernista - Marcondes, Ana Maria Barbosa de Faria (2018)
This work convey an investigation on two moments of the arts in the city of São Paulo, which in the history of art have been treated separately and quite unequally. On the one hand the artists and the art that was exhibited at the 1st General Exhibition of Fine Arts in 1922, on the other hand the Paulista artistic family which entered the scene in the second half of the 1930 's in exhibitions that were the object of many controversy. Nevertheless, they were considered as part of the modernism from São Paulo. The 1922´ year was marked by the expressive event of Modern Art Week in February as well as the 1st General Exhibition of Fine Arts, which was be held in September, in the celebrations of the Centenary and was obscured for posterity. This work is an investigation on the wide web of relations between diverse artists groups that acted in São Paulo. It demonstrates that the generation of artists of 1922 was not just composed by those were present in the Week of Modern Art in the Municipal Theatre in São Paulo. So this investigation pursue to deconstruct the idea that the September Exhibition was an “inexpressive exposition of poor painters”, as mentioned in Klaxon magazine. The investigation of the different layers of the São Paulo artistic movement made possible to recognize a very compact set of actors connected to the Lyceum of Arts and Crafts and to a network of studios. They formed small groups, which since the previous decade, manifested itself in a constant way and possessed technical and aesthetic characteristics shaped by Italian trends from ottocento. Thus, we were able to confirm the hypothesis that the Paulista Artistic Family, which was treated in the historiography of Paulist modernism as an emerging group only in the late 1930s, was already outlined in 1922 or even earlier. It also gained consistency when Paul Claudio Rossi Osir, inspired by the Artistic Family of Milan, gave to the group a new tone, supported by the reception of Mário de Andrade, Sergio Milliet and Paulo Mendes de Almeida. In addition to reconstituting the history of these artists in their relationship with the city of São Paulo, the research sought to trace their engagement to nineteenth-century Italian art. It identifies in Milan and Florence the main artistic environments from which their technical and aesthetic skills derived from. It also links the Paulista artistic Family to the modernist movements of the 1870s, the Milanese Artistic Family and the Florentine macchiaioli. Due to this fact it was fundamental to reconstitute the trajectories of Giuseppe Perissinotto and Cláudio Rossi Osir, who, among others, were the main mediators of the process through which Italian art acclimatized in São Paulo. This research had as methodological tools the sociological concept of the generation of Karl Mannheim and the concept of habitus and field of Pierre Bourdieu. Both they seemed appropriate to test and confirm the hypothesis that the artists of the 1st General Exhibition of Fine Arts were the "other side of the same modernist generation." The Paulista Family of Art was not a movement that arose in 1937, but was another manifestation, among others, of a movement that had been active since the end of 1910. The research was carried out in São Paulo, above all, but also in Florence, Milan and Buenos Aires. In Italian cities we sought to reconstitute the environments through which some of the Italo-Paulist artists passed. In special it was considered the Accademia di Belle Arti di Firenze, where Giovanni Fattori, the principal representative of the Macchiaioli, taught. In Milan, we were able to meet the Famiglia Artistica experience, which had its model reproduced in the city of São Paulo. The research in Buenos Aires was fundamental not only because there also the art of the macchiaioli left expressive traces, but due to the initiatives of Cláudio Rossi Osir to organize exhibitions of Osirarte. In that tile factory he explored the possibilities to transit from traditional media for the scope of applied art involving several artists of the Family Artistic Paulista.When we pay special attention to the tiles, from the monuments that left the drawing board of Victor Dubugras, in São Paulo, to Capanema Palace, Pampulha and Brasília, we tried to conbey that Italian-Paulist artists were important not only in easel painting, but also in the public art of decorative bias that left remarkable marks in the Brazilian landscape